ENVIRONMENTAL EDUCATION AND WATER: CONCEPTS AND EDUCATIONAL PRACTICES IN MUNICIPAL SCHOOLS - Ananias Freitas, Natalia Teixeira [UNESP]; Dias Gomes Marin, Fatima Aparecida [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
The survey Environmental Education and water: concepts and educational practices in municipal schools aimed to identify and evaluate how the water issue is addressed in Elementary School, specifically in the fourth grades., It was investigated how the water theme is approached in: Special Projects in schools, on teaching plans; in Sciences and Geography textbooks and by teachers. This is a qualitative research, such as case studyin which data were collected from documentary analysis of Master Plans of 28 schools and the use of questionnaires and semi-structured interviews with four teachers. Data were analyzed based on the theoretical framework about the water, environmental education and teaching practice. The results obtained in this research indicate the existence of special projects concerning environmental education in ten schools, but they did not specifically address the water. The views and knowledge of the four teachers are mostly based on the contents of textbooks, texts transmitted by the media, and research on the Internet. Educational practices are based on lectures, reading informational texts or contained in textbooks, research and physical-chemical experiments.
Keywords: Environmental Education; Elementary School; Water